EMBRACING TECHNOLOGY IN ESP CLASSES: IS IT A LEARNING TOOL OR JUST COOL TOOL? - Ikrima Halimatus Sa'diyah (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2022)
This study investigated the perceptions of health department students at State Polytechnic of Jember, Indonesia, on how effective Wordwall helps them enrich their English vocabulary during online learning. The researcher used a qualitative approach. Data was collected from ten participants who were chosen based on their activeness while studying and who always participated in the teaching and learning process. It was collected through an open-ended questionnaire distributed via Google Form. Based on the result of the present study, the researcher discovered that the students had positive perception towards the use of Wordwall and they were very enthusiastic about learning vocabulary through the application. The participants also mentioned that this app offers a variety of interactive and creative vocabulary games. The disadvantage is that this application does not provide a place for students to explain their correct and incorrect answers. The students can learn about context and sentence changes by playing games. The result of the study also revealed that Wordwall is an effective learning media for enriching students' vocabulary. Thus, it is suggested that lecturers should utilize this application to help their students become more motivated to learn English vocabulary.